Designing an IoT-based system to detect the out-of-pitch balls in a football match / Muhammad Aniq Abqari Rahizad... [et al.] - Rahizad, Muhammad Aniq Abqari; Razak, Tajul Rosli; Mohd Fauzi, Shukor Sanim; Gining, Ray Adderley JM; Ismail, Mohammad Hafiz (UiTM Cawangan Perlis, 2020)
The incorrect decision-making by the referee made during a football match causes the game unsatisfactory or a biased game. Thus, this problem has become a furious debate among football fans. The fans, as well as players, are dissatisfied when the referee decides specific decisions such as 'a goal or no goal', 'penalty or no penalty' and 'direct red card'. Henceforth, there must be a plan to tackle the problem by using technology, especially in this era. In this paper, as an initial approach, we propose a simple manner of developing a design for the ball out detection using the aid of the IoT (Internet of Things). Specifically, the IoT approach was used for detecting the out-of-pitch balls in a football match. Note that this proposed design was built based on data obtained from a survey questionnaire conducted with the football experts and fans regarding the detection of out-of-pitch balls in a football match. The finding suggested that the proposed design promising to improve the decision-making made in the football match. It is hoped that the study can contribute to the improvement of overall decision making by the referee when coming to the detection of out-of-pitch balls in a football match.